Komunikasi Single Mom dengan Anak Mengenai Pernikahan Kedua - Habibiyah, Afifah Fahrul; Candrasari, Satya (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2024)
A single mom performing a dual role is not an easy thing to do, especially in taking care of and raising children alone. A single mom decided to remarry to be one of the realistic choices of a single mom who wants to have a more decent life and still feel safe because she has a companion. The goal is to find out the process of communication between single moms and children about second marriage. The research methods used in this study are observations and in-depth interviews. The theories and concepts used in this study are, uncertainty reduction theory, and the concept of interpersonal communication. The results of this study suggest that closeness between mother and child can determine the good relationship in it. Interpersonal communication carried out by the mother to the child runs effectively because the mother invites the child to communicate face-to-face even though some of the children do not really like the mother's decision.